Experience of Thyroid Surgery at a Tertiary Care Hospitals in Pakistan - Muhammad Faiz Ullah, Zohaib Akhtar, Arsalan Nasir, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: A goitre is an enlargement of thyroid gland. It may be diffuse or nodular. It can be an isolated solitary nodule with a discrete swelling in one lobe with no palpable abnormality elsewhere or it can be a dominant nodule with discrete swellings and evidence of abnormality elsewhere in the gland. Objectives: The main objective of the study is to find the experience of thyroid surgery at Jinnah Hospital in Pakistan. Material and methods: This cross sectional study was conducted in Jinnah Hospital Lahore during 2021 to 2022. The data was collected from 300 patients who were diagnosed with thyroid cancer and experienced the surgery in the hospital. Demographic information of patients, clinical features and tissue biopsy results were extracted. Results: The data were collected from 300 patients of both genders. The most common presenting symptom was swelling in front of neck, which moved with swallowing. In 85(85%) patients the swelling which was of thyroid origin was benign, while in 15 (15%) patient it was malignant. The type of malignancy on histopathology reports are shown in Table 2. Conclusion: It is concluded that the risk of malignancy in multinodular goitre is not as low as it was thought before and that it is quite significant and is mostly of the papillary type.